Canine circovirus genomic characterization in dogs with and without diarrheal syndrome in Medellín, Colombia - Gomez-Betancur, Diana; Rendon-Marin, Santiago; Giraldo-Ramírez, Sebastian; Jaime, Jairo; Ruiz-Saenz, Julian (Frontiers in Veterinary Science, 2023)
Canine circovirus (CanineCV) is an emerging agent described for the first time in 2011, it infects domestic and wild canids, mainly associated with gastrointestinal signs; however, it has also been reported in samples obtained from animals without clinical signs, so its pathogenesis and epidemiology are still poorly understood. In Colombia, the CanineCV was first reported in 2020 from CPV-2 positive dogs. In the present work, CanineCV was detected in 30% of fecal samples obtained from dogs with or without diarrhea, in the city of Medellín, Colombia. No coinfection with CPV-2 was found. The highest number of positive samples was found in the subgroup of animals with diarrhea. Phylogenetic and evolutionary analyses confirmed the separation of the CanineCV genomes into five different clades with a European origin of the Colombian viruses and at least two different introductions of the CanineCV into the country. Our results highlight the importance of the CanineCV in Colombian dog populations and the need for continue surveillance of emerging pathogens in canine populations.